CHANGING OF COLLECTIVE BARGAINING AGREEMENT BY PARTIES - (:unkn) unknown (ISTANBUL UNIV, FAC LAW, 2016)
Sometimes parties of collective bargaining agreement are not able to arrange entire judicial relations with enough clarity. In this regard, needs of determining in some provisions of agreement would be postponed by parties. After signing the agreement, new situations such as solving the problems or economic changes would create needs for new arrangement. Nowadays, some reasons create difficulties for well-directed arrangement on collective bargaining agreements in terms of union members and between parties. In this situation, following the new conditions and change of defective aspects in the agreement must be unavoidable. In this regard, changing of some provisions in the agreement must be requirement. There is no reason to rule out changes when both sides agree with each other on the agreement although there is no opportunity to force each side for changing the agreement by peace duty. After all, parties cannot modify whatever they wish on the agreement after signing by agreeing with each other. This right subject to some limitation in terms of form and content.
Keywords: The Labor Unions and Collective Bargaining Act; no.6356; Afterwards Changing on Collective Bargaining Agreement